قرارات المجلس الاستشاري الشرعي الوطني للبنك المركزي الماليزي في المعاملات المالية الإسلامية: دراسة تقويمية في ضوء مقاصد الشريعة - Muhammad Najib bin Abdullah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research examines the extent to which the Shariah Resolutions of the Shariah Advisory Council (SAC) of Bank Negara Malaysia in Islamic financial transactions are based on the Maqasid Al-Shari'ah. The study focuses on Islamic banking products in Malaysian banks and is conducted within the framework of the Maqasid Al-Shari'ah rules of Maslahah 'Ammah (Public Interest) and Islah Tadarruji (Incremental Reformation). It also considers the problems related to the resolution of conflict between the theoretical and actual implementation aspects from the Maqasid perspective. This study is based on the analytical, comparative and inductive methods that analyse and discuss the theoretical part of the Islamic scholars' views. The method of field study is conducted through empirically obtained expert interviews regarding the validity and applicability of the Maqasid rules in the resolution and determination of the issues thereunder. The findings of this study show that the resolutions of the SAC, in fact, are based on the Maqasid rules, but it does not contain a proper framework. This must be scrutinized accordingly from the approach of Maslahah 'Ammah and Islah Tadarruji which have a vital role in the formation of the Maqasid framework for Islamic financial law in Malaysia. Such approach is necessary to evaluate the validity of implementation of the resolutions in light of Maqasid Al-Shari'ah in order to reach the desired reforms gradually and holistically in conformity with these ideals.